2008
DOI: 10.1074/jbc.m805392200
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphatase Activity of CthTTM, a Bacterial Triphosphate Tunnel Metalloenzyme

Abstract: Triphosphate tunnel metalloenzymes (TTMs) are a superfamily of phosphotransferases with a distinctive active site located within an eight-stranded ␤ barrel. The best understood family members are the eukaryal RNA triphosphatases, which catalyze the initial step in mRNA capping. The RNA triphosphatases characteristically hydrolyze nucleoside 5-triphosphates in the presence of manganese and are inept at cleaving inorganic tripolyphosphate. We recently identified a TTM protein from the bacterium Clostridium therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 36 publications
3
24
0
Order By: Relevance
“…This is all the more plausible as k cat was even higher for the untagged enzyme (up to 7900 s Ϫ1 at 50°C and pH 9.7, see Table 2). This is 2 orders of magnitude higher than k cat values obtained for CthTTM with its best substrates, PPP i and Gp 4 (12,13). This raises the possibility that in N. europaea the physiological function of NeuTTM might be the degradation of PPP i .…”
Section: Enzyme Prepraration Substrate Conditions Of Experimentsmentioning
confidence: 39%
See 2 more Smart Citations
“…This is all the more plausible as k cat was even higher for the untagged enzyme (up to 7900 s Ϫ1 at 50°C and pH 9.7, see Table 2). This is 2 orders of magnitude higher than k cat values obtained for CthTTM with its best substrates, PPP i and Gp 4 (12,13). This raises the possibility that in N. europaea the physiological function of NeuTTM might be the degradation of PPP i .…”
Section: Enzyme Prepraration Substrate Conditions Of Experimentsmentioning
confidence: 39%
“…In bacteria, two CYTH orthologs were shown to have an adenylyl cyclase activity (4,11,27), but under physiological conditions this activity is low, and its biological significance is not established. CthTTM, the ortholog from C. thermocellum hydrolyzes PPP i with a relatively good turnover (k cat ϭ 3 s Ϫ1 ), but it also hydrolyzes other substrates such as Gp 4 (k cat ϭ 96 s Ϫ1 ) and, to a lesser extent, nucleoside triphosphates and long chain polyphosphates (12,13). Thus, its possible physiological function remains undefined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies of the vaccinia TPase revealed what would emerge as the signature biochemical feature of the TTM-type RNA triphosphatases: the ability to hydrolyze NTP to NDP and P i in the presence of Mn 2+ or Co 2+ (Shuman et al, 1980). The yeast Cet1 structure unveiled a then novel tunnel tertiary structure (Lima et al, 1999) that has since been recognized as the founder of a TTM superfamily that extends well beyond capping enzyme TPases (Gong et al, 2006; Jain and Shuman, 2008). Amino acid sequence comparisons and mutational analyses of metal-dependent RNA triphosphatases of fungi, microsporidia, protozoa and Chlorella virus highlighted conservation of the β strands and essential amino acids that compose the active site tunnel of yeast Cet1, implying a common structure and evolutionary origin for these enzymes (Shuman, 2002), a view later fortified by the structure of mimivirus TPase (Benarroch et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The five top DALI "hits," with relatively feeble Z scores of 3.6 to 4.2, were members of the triphosphate tunnel metalloenzyme (TTM) superfamily of phosphohydrolases, which are composed of an 8-stranded antiparallel β barrel of quite different folding topology (15,16). The TTM barrel has a wider aperture and an extremely hydrophilic interior that binds the divalent cation and polyphosphorylated substrate on which the TTM enzymes act (17).…”
Section: Resultsmentioning
confidence: 99%